UTILIZATION OF BLU-PEA FLOWERS (Clitoria ternatea)AS AN ANTIOXIDANT IN FOOD AND DRINKS IN LUTHU DAYAH KRUENG VILLAGE, SIBREH, ACEH BESAR: PEMANFAATAN BUNGA TELANG (Clitoria ternatea) SEBAGAI ANTIOKSIDAN PADA MAKANAN DAN MINUMAN DI DESA LUTHU DAYAH KRUENG, SIBREH, ACEH BESAR - Widya Angreni; Erda Marniza; Rina Kurniaty; Resmila Dewi; Cut Suraiya Wahyuni Utami (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
This Community Service activity was carried out in Luthu Dayah Krueng Village, Sibreh, Aceh Besar Regency, on February 10, 2022, with the theme of Utilization of Butterfly Pea Flowers (Clitoria ternatea) as Antioxidants in Food and Beverages. The target of this program was residents of Luthu Dayah Krueng Village, totaling 40 people aged 30 to 70, including men and women. In its implementation, the methods used were lectures, demonstrations, and question-and-answer sessions. Overall, the implementation of this community activity program went well, was safe, and adhered to procedures. It is hoped that the results of this Community Service activity will deepen the community’s understanding of the proper use of Butterfly Pea Flowers (Clitoria ternatea) to be made into food products, especially food and beverages.